2019
DOI: 10.1038/s41467-019-09794-7
|View full text |Cite
|
Sign up to set email alerts
|

Spectra stable blue perovskite light-emitting diodes

Abstract: Device performance and in particular device stability for blue perovskite light-emitting diodes (PeLEDs) remain considerable challenges for the whole community. In this manuscript, we conceive an approach by tuning the ‘A-site’ cation composition of perovskites to develop blue-emitters. We herein report a Rubidium-Cesium alloyed, quasi-two-dimensional perovskite and demonstrate its great potential for pure-blue PeLED applications. Composition engineering and in-situ passivation are conducted to further improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
301
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 388 publications
(324 citation statements)
references
References 51 publications
(68 reference statements)
5
301
2
Order By: Relevance
“…Liang et al improved the crystal quality by converting poly‐crystalline PEA 2 PbBr 4 thin films into single‐crystalline micro‐sized nanoplates via solvent vapor annealing and showed efficient room‐temperature violet EL at 410 nm (Figure A) . Compared to the pure phase RP perovskite components (one value of n only), poly‐crystalline RP perovskite films containing multiple phases (multiple values of n) have superior light‐emission performance . Yuan et al and Huang et al independently reported LEDs incorporated with mixed layered perovskite materials, displaying impressive performance and stability.…”
Section: Metal Halide Perovskitesmentioning
confidence: 99%
See 4 more Smart Citations
“…Liang et al improved the crystal quality by converting poly‐crystalline PEA 2 PbBr 4 thin films into single‐crystalline micro‐sized nanoplates via solvent vapor annealing and showed efficient room‐temperature violet EL at 410 nm (Figure A) . Compared to the pure phase RP perovskite components (one value of n only), poly‐crystalline RP perovskite films containing multiple phases (multiple values of n) have superior light‐emission performance . Yuan et al and Huang et al independently reported LEDs incorporated with mixed layered perovskite materials, displaying impressive performance and stability.…”
Section: Metal Halide Perovskitesmentioning
confidence: 99%
“…The mixed compounds act like a photocarrier concentrator, funneling the charge carriers from high‐bandgap materials to the lowest‐bandgap ones and boosting the external quantum efficiency (EQE) to 8.8% and 11.7% (Figure B‐C), respectively . Jiang et al tuned the “A‐site” cation by using a Rubidium‐Cesium alloyed perovskite, demonstrating a spectra‐stable blue LED with a peak EQE of 1.35% (Figure D) . In addition to the composition engineering, other strategies like surface passivation, crystallite tailoring, structure engineering, and so forth were also applied for performance and longevity improvement .…”
Section: Metal Halide Perovskitesmentioning
confidence: 99%
See 3 more Smart Citations